Morphological Determinants of Carbon Nanomaterial-Induced Amyloid Peptide Self-Assembly - Xing, Yanting; Sun, Yunxiang; Wang, Bo; Ding, Feng (Frontiers in Chemistry, 2020)
Hybridizing carbon nanomaterials (CNMs) with amyloid fibrils – the ordered nanostructures self-assembled by amyloidogenic peptides – has found promising applications in bionanotechology. Understanding fundamental interactions of CNMs with amyloid peptides and uncovering the determinants of their self-assembly structures and dynamics are, therefore, pivotal for enriching and enabling this novel class of hybrid nanomaterials. Here, we applied atomistic molecular dynamics simulations to investigate the self-assembly of two amyloid peptides - the amyloidogenic core residues 16-22 of amyloid-β (Aβ16-22) and the non-amyloid-β core of α-synuclein (NACore68-78) - on the surface of carbon nanotubes (CNT) with different sizes and chirality. Our computational results showed that with small radial CNTs, both types of peptides could form β-sheets wrapping around the nanotube surface into a supercoiled morphology. The angle between β-strands and nanotube axes in the supercoil structure depended mainly on the peptide sequence and CNT radius, but also weakly on the CNT chirality. Large radial CNTs and the extreme case of the flat graphene nanosheet, on the other hand, could nucleate amyloid fibrils perpendicular to the surface. Our results provided new insights of hybridizing CNMs with amyloid peptides and also offered a novel approach to manipulate the morphology of CNM-induced amyloid assembly by tuning the surface curvature, peptide sequence, and molecular ratio between peptides and available CNM surface area, which may be useful in engineering nanocomposites with high-order structures.